The impact of big five personality traits on salespeople’s performance: exploring the moderating role of culture - Yakasai, Abubakar Mukhtar; Jan, Muhammad Tahir (Sohar University, Oman and American University of Kuwait, 2015)
Purpose - The aim of this paper is to examine the impact of Big Five Factor of personality traits on salespeople’s’ performance, taking into consideration the mediating role of customer orientation, as well as exploring the moderating role of culture. Design/Methodology/Approach – The Big Five Factor (BFF) of personality traits was used in this paper base on salespeople’s performance literature. This paper proposed a framework with customer orientation as a mediating factor and culture as a moderating factor of salespeople’s performance. Findings – Research on salespeople’s performance is an ongoing process, which has attracted much attention from various stakeholders to find out befitting combination of factors for effective salespeople’s performance. This paper found out that no specific sets of factors could lead to effective salespeople’s performance in all situations because performance is a context-based outcome. The big five factor alone cannot effectively explain salespeople’s performance. Salespeople’s customer orientation can play a significant mediating role in the big five-factor framework in predicting salespeople’s performance. Additionally, the moderating effect of salespeople’s culture in the proposed model is revealed to help enormously in determining differences, if any, in the salespeople’s performance. Originality/value - The in-depth review of different factors influencing salespeople’s performance helps practitioners (such as sales managers, executives, supervisors, as well as human resource managers) by signifying which combinations of factors can best predict better salespeople’s’ performance in particular instances, hence assist proper decision as regards to potential sales team. In addition, the proposed framework in this paper helps researchers by providing a tool for systematic evaluation and testing of real empirical situation of salespeople’s’ performance.